Exploring a Review of Factors Affecting Work-Life Balance of Employees in the Chinese Banking Sector - Wu, Sitong; Fauzi, Nor Fairuz Syazana Binti Nor (Journal of Theory and Practice in Economics and Management, 2025)
This study systematically analyses the influencing factors of work-life balance and their mechanisms of action for employees in the Chinese banking industry. It is found that the degree of fulfillment of the psychological contract, the level of employees’ resilience, and decent work practices have a direct impact on work-life balance; employees’ self-regulation ability plays a moderating role between stress and work-life balance, and perceived job satisfaction is an important mediator of the above factors affecting work-life balance. Taking into account the special cultural context and institutional environment of China’s banking industry, this paper proposes an integrative theoretical framework that emphasizes the systematic improvement of employee well-being through optimizing the psychological contract, enhancing employee resilience, refining decent practices, and focusing on culturally appropriate policies.